HUBUNGAN MINAT DENGAN TINGKAT KEBUGARAN JASMANI BERMAIN SEPAK BOLA - Wayan Adnyana; Suranto Suranto; Heru Sulistianta (JUPE (Jurnal Penjaskesrek), 2015)
This study aims to look at the contribution of the relationship of interest and level of physical fitness to play football. The methodology of the study is descriptive correlation data analysis simple linear regression. Collecting data using questionnaires, the sample used from 30 population is hindu youth banjar puspasari amounted to 30 people. The results obtained by analysis of the significance level of 0,000b which means significant value obtained is less than 0.05 and even 0.01, so that H0 is rejected at the 0.05 significance level and 0.01 or Fhit F table (170.606 4.20), so there is a relationship which significantly between the interest level of physical fitness to play football. Conclusion This study shows that the interest in having a relationship with the level of physical fitness.Penelitian ini bertujuan untuk melihat sumbangan atas hubungan minat dan tingkat kebugaran jasmani bermain sepakbola. Metodelogi penelitian yang digunakan adalah deskriptif korelasi dengan analisis data regresi linier sederhana. Pengumpulan data menggunakan angket, sampel yang digunakan dari 30 populasi adalah pemuda hindu banjar puspasari berjumlah 30 orang. Hasil analisis diperoleh taraf signifikansi 0,000b yang artinya nilai signifikan yang didapat kurang dari 0,05 bahkan 0,01, sehingga H0 ditolak pada tingkat signifikansi 0.05 maupun 0,01 atau Fhit Ftabel (170,6064,20), jadi ada hubungan yang signifikan antara minat dengan tingkat kebugaran jasmani bermain sepakbola. Kesimpulan penelitian ini menunjukan bahwa minat memiliki hubungan dengan tingkat kebugaran jasmani.Kata kunci : kebugaran jasamani, minat, sepakbola